Keefektifan Model Pembelajaran Kooperatif Tipe Think Talk Write Berbantuan Media Mind Mapping Mahasiswa Pendidikan Biologi - Thahir, Rahmatia; Anisa, Anisa; Magfirah, Nurul (Hybrid: Jurnal Pendidikan dan Pembelajaran Sains, 2022)
The goal to be achieved in this study is to determine the effectiveness of learning the concept of Animal Diversity through the application of the think talk write (TTW) cooperative learning model assisted by mind mapping media for biology education students. This type of research is research that is Pre-Experimental Design. The research design used in this study is the One Group Pretest-Posttest Design. The instruments used in this study were observation sheets of learning activities; Observation sheets containing indicators of learning activities are used to assess student learning activities at each meeting, and test questions of learning outcomes; The learning outcomes test is in the form of 30 multiple choice questions with 5 answer choices. Based on the results of data analysis and discussion, it can be concluded that the application of the TTW type cooperative learning model assisted by mind mapping media is effectively applied in biology learning the concept of Animal Diversity in class A students of the 2017 Biology Education FKIP Unismuh Makassar.